Enhancing Spiritual Resilience among Gen Z Muslims: The Role of Contextualized Islamic Curriculum Innovation - Mu'min, U Abdullah; M. Renaldy Fadilah; Muhammad Haikal (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2025)
This study aims to analyze and develop a contextual curriculum design in Islamic Religious Education (IRE) oriented to the mastery of spiritual science Generation Z students in SMP IT Sahabat Alam. Generation Z, often characterized as a highly digital generation, faces distinctive challenges related to spirituality, including issues of religiosity, technology integration, and identity formation. Using a qualitative approach with a case study design, data were collected through classroom observations, in-depth interviews with PAI teachers and students, and analyses of curriculum documents and instructional materials. The findings indicate that the contextual PAI curriculum design aligns learning materials with students’ everyday realities, thereby enhancing the relevance, applicability, and depth of their understanding. The integration of environmental issues, digital technology, and contemporary social dynamics into PAI content contributes to strengthening students’ spiritual values within their present context. Furthermore, the use of reflection-based learning strategies, open discussions, and integrated social projects proved effective in cultivating spiritual awareness that is adaptive and resilient to external influences. This study highlights the importance of developing a context-based PAI curriculum as a strategic response to the demands of 21st-century education, particularly for Generation Z learners who inhabit an increasingly digital and pluralistic environment